2005
DOI: 10.1021/es048085h
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Emission of Particles from a Diesel Engine by Adding an Oxygenate to the Fuel

Abstract: Particulate and high emissions of NO x are the main problems that are associated with diesel engines. Therefore, techniques and fuels that promote a reduction in these emissions currently are attracting great interest. In this paper, a mixture of acetal and regular diesel fuel has been tested in a heavy-duty diesel engine. The effect was a marked decrease in particle number and the estimated particle mass. A small reduction of the engine power was also observed; however, the net effect was nevertheless a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Conversely, cyclic hydrocarbons have higher energy densities, due to ring strain, and are preferred to be mixed into conventional jet‐fuel to increase its density . Past investigations have also found that the addition of oxygenates to fuel, in which the oxygen is bonded to two carbons as with ethers and esters, yield the lowest soot emissions of particulate matter and emissions decline as the oxygen content is increased . In addition, it has been found that when a cyclic ketone is added at a constant concentration to a heavy‐duty direct injection diesel engine, the smoke opacity and soot emissions are lowered .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, cyclic hydrocarbons have higher energy densities, due to ring strain, and are preferred to be mixed into conventional jet‐fuel to increase its density . Past investigations have also found that the addition of oxygenates to fuel, in which the oxygen is bonded to two carbons as with ethers and esters, yield the lowest soot emissions of particulate matter and emissions decline as the oxygen content is increased . In addition, it has been found that when a cyclic ketone is added at a constant concentration to a heavy‐duty direct injection diesel engine, the smoke opacity and soot emissions are lowered .…”
Section: Introductionmentioning
confidence: 99%
“…At 2300 r$min -1 , the percentages of ultra-fine particle were 66%-82% for diesel fuel and 73%-88% for A-diesel. The opposite results were reported by Nord et al [14]. In their study, a 10% acetal blend with diesel fuel (A-diesel) and base diesel fuel were tested on a diesel engine with electronically controlled fuel injection.…”
Section: Resultsmentioning
confidence: 62%
“…Nowadays, 1,1-dibutoxyethane (DBE) and other similar acetals such as dibutoxymethane derived from n-butanol and formaldehyde are produced at a small scale, mainly for applications in the flavor and fragrance industries and as solvents (cleaning, aerosols, adhesives, etc.). Acetals have also been identified as oxygenates for diesel blending due to their capability to reduce emissions, mainly of particulate matter, and to facilitate the combustion of the final products without decreasing the ignition quality, maintaining, or even increasing the cetane number [10,11]. Acetals have also been identified as oxygenates for diesel blending due to their capability to reduce emissions, mainly of particulate matter, and to facilitate the combustion of the final products without decreasing the ignition quality, maintaining, or even increasing the cetane number [10,11].…”
Section: Generalmentioning
confidence: 99%